High‐Performance Ruthenium Sensitizers Containing Imidazolium Counterions for Efficient Dye Sensitization in Water. Issue 14 (21st June 2017) - Li, Xiaoyu; Li, Shiqing; Gao, Ge; Wu, Di; Lan, Jingbo; Wang, Ruilin; You, Jingsong
Abstract: A new type of water‐soluble ruthenium sensitizers incorporating imidazolium counterions, denoted [DMPI]2 −Ru and [DMHI]2 −Ru, has been developed, which can be efficiently adsorbed onto TiO2 photoanodes in aqueous solution. Owing to the good thermal stability of imidazolium, [DMPI]2 −Ru adsorbed on TiO2 has a higher decomposition temperature than N719 dye [di(tetrabutylammonium) cis ‐di(thiocyanato)bis(2, 2′‐bipyridine‐4, 4′‐dicarboxylato)ruthenium(II)]. When using organic solvent‐based I − /I3 − electrolytes, solars cell based on [DMPI]2 −Ru‐sensitized TiO2 in water show high power conversion efficiencies (PCE) of up to 10.2 %, which is higher than that of N719 (9.9 %) under the common conditions for dye sensitization in organic solvent. [DMHI]2 −Ru, with poorer water solubility than [DMPI]2 −Ru, gives a smaller dye‐adsorption amount on TiO2 and thus a lower PCE of 9.4 %. From the viewpoint of safety and environmental impact, the fabrication of dye‐sensitized solar cells (DSSCs) by using water as solvent is undoubtedly a preferable strategy. Although the [DMPI]2 −Ru‐based device fabricated by using water as the solvent for both the dye‐sensitization process and the electrolyte gives a relatively low efficiency, it provides a promising approach for the practical application of DSSCs. Abstract : Another way to dye : A new type of ruthenium sensitizers has been developed by replacing the tetrabutylammonium cations of N719 dye with imidazolium cations. Owing to the high hydrophilicity and good thermal stability of the imidazolium cation, these new sensitizers exhibit good water solubilities and thermal stabilities. They can be efficiently adsorbed onto TiO2 photoanodes in aqueous solution and show high power conversion efficiencies (up to 10.2 %).